Design of the Worker Profiling and Reemployment Services System and Evaluation in Michigan - Randall W. Eberts; Christopher J. O'Leary (W.E. Upjohn Institute for Employment Research, 1996)
The Unemployment Compensation Amendments of 1993, Public Law 103-152, require each state employment security agency to implement a Worker Profiling and Reemployment Services (WPRS) system. WPRS systems are intended to identify unemployment insurance beneficiaries who are most likely to exhaust their regular benefits, and refer them quickly to reemployment services to speed the transition to new employment. This brief paper was prepared for a national colloquium on WPRS held June 11-14, 1996 in Atlanta. The paper summarizes work done by the W.E. Upjohn Institute for Employment Research for the State of Michigan to design and implement a UI profiling model, and to design an evaluation of the WPRS system effectiveness.
Keywords: J0; J6; 330; unemployment; insurance; reemployment; Eberts; O'Leary